Comparative performance of Landrace, Yorkshire and Duroc breeds of swine - Zebua, C. K. N.; Muladno, M.; Siagian, P. H. (Diponegoro University, 2017)
The objectives of this study was to analyze the comparative ability of animal genetic, using evaluation of production that has important economic traits including Landrace, Yorkshire, and Duroc breeds of swine. A total of 49 swine consist 15 boars and 34 gilts, with average body weight of 18.50-21.50kg were used in this research. All of samples were raised in the same pen and feeding management. This research used the experimental method of Completely Randomized Design involving three treatments of animal breeds including Landrace, Yorkshire, and Duroc breeds. The data were analyzed by using analysis of covariance procedur General Linier Model and Least Square Means test. Boars and gilts were analyzed in separated data. The result showed that the effect of breed was significantly associated for all traits, but not for boars feed intake. The overall, Yorkshire and Landrace performed better than Duroc for average daily gain, feed conversion ratio, selection index, and age at 90 kg body weight. However, Duroc boars and gilts had the thinnest backfat followed by Yorkshire and Landrace.